BUDAYA BELAJAR MATEMATIKA SISWA SMA NEGERI 1 PRAMBANAN - SUPARNO, SUPARNO (2011)
Global research purpose is to describe mathematic learning culture student 1 Government Senior High School Prambanan. Specific research purposes are; (1) to describe student mathematic learning culture in class learning process. (2) to describe student mathematic learning culture at home. (3) to describe student mathematic learning culture in society. This research is qualitative research. Research has done in 1 Government Senior High School Prambanan. Collecting data techniques used were participation observation, interview, and documentation. Analysis in qualitative research is including 3 main components which are data reduction, data presentation, and verification. Research results are (1) Culture of mathematics learning in the learning process is an effort to follow the learning of mathematics students in accordance with the norms set by the teacher, in the form of a compliance culture, innovative culture, and cultural achievement. Compliance culture is manifested in the form of obedience to the students of learning time, learning discipline, devotion and loyalty to the discipline of learning, students' willingness to improve the quality of learning and a sense of completion in the study. Innovative culture in the form of students' habits in using a variety of ways to solve the problem of learning. Culture is the habit of student achievement of Senior High School Prambanan to achieve good performance and mastery learning in mathematics. (2) Student mathematic learning culture at home is different each other because they have different culture. Different way in making comfortable situation is caused by student need to make comfortable situation for learning. This situation is based on family support including giving facility, tools and infrastructure and also free time to study. (3) Student mathematic learning process in society is according to society support and tools also infrastructure in it. Student culture in learning in the middle of society can be done in group, everyday from 4 pm until 6 pm and following any learning programs.